Willem van Bennekom, De jaren van Maarten van Traa - J.W.L. Brouwer (BMGN: Low Countries Historical Review, 2017)
Willem van Bennekom, De jaren van Maarten van Traa (Amsterdam: Boom, 2015, 591 pp., isbn 978 908 953 641 9).